2020
DOI: 10.1177/1043659620935970
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic Parental Beliefs and Practices in the Management of Common Childhood Illnesses: A Review of the Literature

Abstract: Introduction: Hispanic parents are more likely to perceive common childhood illnesses as serious and needing immediate attention compared with other groups. The purpose of this review is to describe the factors that influence Hispanic parental management of common childhood illnesses. Method: A systematic search of PubMed, PsycINFO, and Cumulative Index of Nursing and Allied Health Literature was conducted. Studies were screened and reported according to the Preferred Reporting Items for Systematic Reviews and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…When navigating fever, parents employed biomedical and folk-related treatments simultaneously. Contrary to previous studies, none of the parents in this study used folk healers to treat fever; however, some employed their grandparents and great-grandparents to conduct healing rituals (Acorda et al, 2020; Fowler et al, 2021). Very few parents were comfortable treating recurring fever at home and most sought care immediately after the first fever episode.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…When navigating fever, parents employed biomedical and folk-related treatments simultaneously. Contrary to previous studies, none of the parents in this study used folk healers to treat fever; however, some employed their grandparents and great-grandparents to conduct healing rituals (Acorda et al, 2020; Fowler et al, 2021). Very few parents were comfortable treating recurring fever at home and most sought care immediately after the first fever episode.…”
Section: Discussionmentioning
confidence: 71%
“…Understanding family dynamics and engaging other members when discussing management may help to reinforce good practices and lessen fears. The influence of media sources on parental beliefs and practices was a unique finding in this study; previous studies identified in a systematic review on Hispanic beliefs did not explore or find the media as a source of information (Acorda et al, 2020). However, parents still preferred receiving fever information from their health care providers.…”
Section: Discussionmentioning
confidence: 78%
“…These findings are consistent with previous research on health disparities among minority groups. For example, similar attitudes were shown by Hispanic parents who hesitated to share their folk-related practices on common childhood illnesses with HCP(Acorda et al, 2020).…”
mentioning
confidence: 76%
“…Though participants often used foods to resolve minor health issues, many voiced waiting until their child was at least 1 year old to use home remedies they viewed as riskier (e.g., herbal teas). Using remedios caseros (home remedies), including giving infants dietary botanical supplements, is a common practice among US Latinx individuals (Acorda et al, 2020 ). However, the use of foods as remedios caseros on infants and toddlers among Latinx mothers is understudied.…”
Section: Discussionmentioning
confidence: 99%